Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Produk Skincare: Persepektif Social Media Marketing, Kualitas Produk, Dan Persepsi Harga - Afriyani Dwi Tanti; Edy Nursanta; Widiyarsih; Siti Masitoh (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to analyze the influence of social media marketing, product quality and price perceptions on purchasing decisions for skincare products (Study of users of The Originote skincare products in Tangerang City). The analysis method in this research uses quantitative primary data, the test stages carried out are validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression analysis, coefficient of determination, t test and F test. The data used in this research uses questionnaire instruments, and Valid data was collected from 120 respondents. The sampling method in this research was purposive sampling. The testing tool used is SPSS Version 26. The results of the research show that the variables Social Media Marketing, Product Quality, and Price Perception partially influence the decision to purchase The Originote Skincare product. The results of the research show that the variables Social Media Marketing, Product Quality, and Price Perception simultaneously influence purchasing decisions for The Originote Skincare products.